2022
DOI: 10.15586/ijfs.v34i3.2238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion processing conditions on the techno-functional, antioxidant, textural properties and storage stability of wholegrain-based breakfast cereal incorporated with Indian horse chestnut flour

Abstract: The central composite rotatable design was used to plan the experiments using feed moisture (FM) content, barrel temperature (BT), screw speed (SS), and concentration of Indian horse chestnut flour (IHCF) as process variables varied between 10–18%, 70–150°C, 290–380 rpm and 1.75–4.75%, respectively. Surface mechanical energy, water holding capacity, swelling volume, piece density, longitudinal expansion, water activity and colour attributes were used as response variables. The whole grain flours added with 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This can be attributed to the changes in the material viscosity in the barrel due to the increased shear. Ma et al [50] extruded wheat flour with various co-rotating twin-screw extruders and they found decreased SME when the water content increased from 18 to 24% at both die temperatures of 95 • C and 139 • C. Allai et al [53] also reported upon the effect of processing conditions on SME during the extrusion of wholegrain breakfast cereals. Here, feed moisture content and barrel temperature were found to be inversely proportional to SME.…”
Section: Effect Of Variables On Extrusion Performancementioning
confidence: 99%
“…This can be attributed to the changes in the material viscosity in the barrel due to the increased shear. Ma et al [50] extruded wheat flour with various co-rotating twin-screw extruders and they found decreased SME when the water content increased from 18 to 24% at both die temperatures of 95 • C and 139 • C. Allai et al [53] also reported upon the effect of processing conditions on SME during the extrusion of wholegrain breakfast cereals. Here, feed moisture content and barrel temperature were found to be inversely proportional to SME.…”
Section: Effect Of Variables On Extrusion Performancementioning
confidence: 99%
“…The color of powdered extrudates was evaluated using a ColorQuest (Hunter-Lab, Reston, VA, USA) colorimeter, working with xenon lamp illumination and an 8° angle as described by Allai et al (2022). Prior to taking assessments, the instrument was set up against a reference white tile.…”
Section: Colormentioning
confidence: 99%
“…Many studies investigated the effects of extrusion on the antioxidant activity of cereals, fruits, legumes, vegetables, and seeds (Table 5). Allai et al [140] found that the extrusion of wheat, barley, Indian horse chestnut flour, and their mixes caused the reduction in antioxidant activity compared to the raw materials due to the changes in the bioactive compounds' chemical structure and polymerization reactions. Another study reported a positive influence of the screw speed on the chicory-rice blend's antioxidant activity, while the increase in moisture led to lower antioxidant properties of the mix [141].…”
Section: Effects Of Extrusion On the Biological Activitymentioning
confidence: 99%